A universal method for direct PCR amplification of plant tissues. Issue 11 (6th March 2017) - Li, Yuping; Zhao, Huanhuan; Yan, Xuefen; Li, Meng; Chen, Peng; Zhang, Suiqi
Abstract : PCR is a vital tool in modern biology; however, it can be costly owing to the price of commercial DNA purification kits. Abstract : PCR is a vital tool in modern biology; however, it can be costly owing to the price of commercial DNA purification kits. DNA purification is time consuming and rare material used for DNA template purification during transgenic mutant screening can be risky. There is, therefore, an urgent need to develop alternative approaches. Here, we describe a convenient and efficient method for direct PCR amplification of plant tissues. In this method, plant tissue samples are obtained using micropipettes and, after incubation with a casein alkaline solution, are used directly as DNA templates for PCR. In addition, 20 mM ammonium sulfate and a high-fidelity DNA polymerase fused to sso7d (a small DNA-binding protein) are essential components of this system. We applied this method to tartary buckwheat, which is rich in secondary metabolites, and we found this method to be effective in maize, wheat, Arabidopsis, and tobacco. All the steps of the protocol can be carried out on a thermal cycler. Moreover, the minor injuries to the plants when collecting samples have no effect on their growth and survival. Our new protocol offers a considerable simplification of present direct PCR approaches and it will be particularly useful for screening transgenic mutants and trace amounts of precious materials.